The Pashtun question : the unresolved key to the future of Pakistan and Afghanistan - Siddique, Abubakar (Hurst, 2014)
"Most contemporary journalistic and scholarly accounts of the instability gripping Afghanistan and Pakistan have argued that violent Islamic extremism, including support for the Taliban and related groups, is either rooted in Pashtun history and culture, or finds willing hosts among their communities on both sides of the Afghanistan-Pakistan border. Abubakar Siddique sets out to demonstrate that the failure, or even unwillingness, of both Afghanistan and Pakistan to absorb the Pashtuns into their state structures and to incorporate them into the economic and political fabric is central to these dynamics, and a critical failure of nation- and state-building in both states. In his book he argues that religious extremism is the product of these critical failures and that responsibility for the situation lies to some degree with the elites of both countries. Partly an eye-witness account and partly meticulously researched scholarship, The Pashtun Question describes a people whose destiny will shape the future of Pakistan and Afghanistan."--